Imaging and Baseline Predictors of Cognitive Performance in Minor Ischemic Stroke and Patients With Transient Ischemic Attack at 90 Days. Issue 3 (March 2016) - Mandzia, Jennifer L.; Smith, Eric E.; Horton, Myles; Hanly, Patrick; Barber, Philip A.; Godzwon, Catherine; Donaldson, Emily; Asdaghi, Negar; Patel, Shiel; Coutts, Shelagh B.
Abstract : Background and Purpose—: Few studies have examined predictors of cognitive impairment after minor ischemic stroke and transient ischemic attack (TIA). We examined clinical and imaging features associated with worse cognitive performance at 90 days. Methods—: TIA or patients with minor stroke underwent neuropsychological testing 90 days post event. Z scores were calculated for cognitive tests, and then grouped into domains of executive function (EF), psychomotor processing speed (PS), and memory. White matter hyperintensity and diffusion-weighted imaging volumes were measured on baseline magnetic resonance imaging. Ninety-day outcomes included modified Rankin Scale (mRS) and Centre for Epidemiological Studies Depression Scale (CES-D) score. Results—: Ninety-two patients were included, 76% male, 54% TIA, and mean age 65.1±12.0. Sixty-four percent were diffusion-weighted imaging positive. Median domain z scores were not significantly different from published norms ( P >0.05): memory −0.03, EF −0.12, and PS −0.05. Patient performance ≥1 SD below normal was 20% on memory, 16% on PS, and 17% on EF. Cognitive scores did not differ by diagnosis (stroke versus TIA), stroke pathogenesis, presence of obstructive sleep apnea, and diffusion-weighted imaging or white matter hyperintensity volumes. In multivariable analyses, lower EF was associated with previous cortical infarct on magnetic resonance imaging ( P =0.03), mRS score of >1; P =0.0003 and depressive symptoms (CES-D ≥16; P =0.03). Lower PS scores were associated with previous cortical infarct ( P =0.02), acute bilateral positive diffusion-weighted imaging ( P =0.02), mRS score of >1 ( P =0.003), and CES-D ≥16 ( P =0.03). Conclusions—: Despite average-range cognitive performance in this TIA and population with minor stroke, we found associations of EF and PS with evidence of previous stroke, postevent disability, and depression. Abstract : Supplemental Digital Content is available in the text.